2022
DOI: 10.3389/fnhum.2022.838645
|View full text |Cite
|
Sign up to set email alerts
|

General and Specific Dimensions of Mood Symptoms Are Associated With Impairments in Common Executive Function in Adolescence and Young Adulthood

Abstract: Both unipolar and bipolar depression have been linked with impairments in executive functioning (EF). In particular, mood symptom severity is associated with differences in common EF, a latent measure of general EF abilities. The relationship between mood disorders and EF is particularly salient in adolescence and young adulthood when the ongoing development of EF intersects with a higher risk of mood disorder onset. However, it remains unclear if common EF impairments have associations with specific symptom d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 71 publications
(119 reference statements)
0
2
0
Order By: Relevance
“…Although the sexual minority group likely only accounted for a small proportion of the overall group, it may have been an important factor affecting the emotional state of adolescents and early adults. Fourth, this study did not conduct a dimensional categorical analysis of the specific symptoms of depression and anxiety, considering the youthful attributes of the study population, and it did not conduct a systematic investigation and correlation analysis of cognitive function, even though other studies have shown that unipolar depression and bipolar depression in adolescence and early adulthood are associated with impaired executive functioning ( 32 ). Finally, depression and anxiety may be related to other factors that were not considered in this study, due to the characteristics of the study sample.…”
Section: Limitationsmentioning
confidence: 99%
“…Although the sexual minority group likely only accounted for a small proportion of the overall group, it may have been an important factor affecting the emotional state of adolescents and early adults. Fourth, this study did not conduct a dimensional categorical analysis of the specific symptoms of depression and anxiety, considering the youthful attributes of the study population, and it did not conduct a systematic investigation and correlation analysis of cognitive function, even though other studies have shown that unipolar depression and bipolar depression in adolescence and early adulthood are associated with impaired executive functioning ( 32 ). Finally, depression and anxiety may be related to other factors that were not considered in this study, due to the characteristics of the study sample.…”
Section: Limitationsmentioning
confidence: 99%
“…Such deficits have been observed at comparable effect sizes across subdimensions of executive functioning, suggesting mood-related impairment in “common” executive functioning that broadly disrupts goal-directed behavior (Snyder, 2013). In turn, common executive dysfunction is observed across mood disorders (Snyder et al, 2019), putatively driving shared psychopathological processes that correspond with distress, overlapping symptoms, or symptom severity (Peterson et al, 2022). Critically, poor executive functioning may be a risk marker for future mood pathology.…”
mentioning
confidence: 99%